PERANCANGAN IKLAN KOMERSIAL PERURI SIGN DAN PERURI TERA DENGAN FORMAT TELEVISI OLEH CAMERA PERSON - Kalam Aryo Yudo; Ika Sartika; Mulyono (LAYAR: Jurnal Ilmiah Seni Media Rekam, 2024)
The production of an attractive advertisement requires a very complex design. Therefore, a design is needed on how to design an advertisement, especially the design of a camera person on a Peruri commercial advertising video with a television format. This final report aims to provide information on how to design Peruri sign and Peruri tera commercial advertisements with a television format. The design of Peruri commercial advertisements with a television format carried out by a camera person through three stages. The first stage of design, the second stage of recording and the last stage is the post-recording stage. The results of designing Peruri commercial advertisements with television formats carried out by camera people are making 4K image formats in order to meet television standards and in recording images camera people record more images with medium angle techniques and dolly movements. The results of this final report can be used as a reference in producing an advertisement with a television format.